Integration of Marriage Age Legal Education in School Environments to Support Children’s Rights to Education and Health - Dian Latifiani; Fitri Indrawati; Yustina Dhian Novita (Semarang State University Undergraduate Law and Society Review, 2026)
Junior High School (SMP) plays a crucial role in a student’s educational path. SMP is a bridge between elementary school (SD) and high school (SMA), which forms an important foundation for students’ academic, social, and emotional development. The problem Initial investigation results revealed child marriage at SMPN 1 Pemalang. Both the bride and groom, both male and female, were still 14 years old, which means that the marriage violated the minimum age for marriage according to the law. The target community is not yet fully aware of the existence of alternative solutions for children who drop out of school due to child marriage, so their right to education is neglected. Children who marry at an early age are also not yet able to fully understand the negative impacts of marriage under the age of 19, such as poverty, domestic violence (KDRT), and health problems. The complexity of the problem of child marriage is not comparable to the psychological condition of children who are not yet mature, which has a negative impact on their mental health and ultimately reduces the quality of Indonesia’s human resources (HR). To overcome this problem, the devotee offers a solution in the form of ongoing activities that focus on Increasing Legal Awareness of Marriage Age to Fulfill Education and Health Rights at Smp Negeri 1 Pemalang. The target of this program is to increase legal awareness related to the ideal marriage age and solutions through educational forums, which will be measured through a post-test with a target value higher than the survey and pre-test results.